آليات التحول نحو اقتصاد المعرفة في التعليم المهني في العراق (المجلة العراقية للعلوم الاقتصادية, 2018)
The world is witnessing a revolution of knowledge emerged from rapid developments in information and communication technology, which played a key role in the trend towards knowledge economies, that have helped to a deeper understanding of the role of knowledge and human capital in the process of economic and social development, hence there is an increasing need for a shift towards a knowledge economy as field a New in general, ingeneral and vocational education in Iraq in particular because of its role in the shift towards the acquisition and promotion of competitive advantage, and then effechve corlribution to the actor in the process of economic development by keeping up vocational education for the knowledge economy and the development of its infrastructure .